Efeito da suplementação protéico-energética-mineral com uréia convencional ou de liberação lenta no desempenho e eficiência econômica de bovinos de corte no período seco do ano - Diego Palucci Pantoni (2012)
This experiment was designed a determine the effects of weight gain, consumption and economic analysis of protein-energy supplementation and mineral (SPEM) and the replacement of urea by the conventional slow-release urea (ULL) in finishing cattle, during the dry pastures of Brachiaria brizantha cv. Marandu. 40 bulls were used (Nellore) with an average of 446 kg initial live weight (PVI). For evaluation of total dry matter intake (CSMT) and forage (CSMF) 20 bulls were used with whole 460.9 kg (PVI). The treatments were: control (T1), protein supplements - energy - (Urea, Soybean Meal, Ground Corn, mineral) (T2), protein supplements - energy (Urea, Urea slow release, Soybean Meal, Ground Corn, mineral) (T3) and protein supplement - energy - (Slow Release Urea, Soybean Meal, Ground Corn, mineral) with average intake of 1 kg / head / day. The experimental design was completely randomized. The data were subjected to analysis of variance and means were compared by Tukey test at 5% probability. A significant effect of weight gain in SPE. There was no effect on the SPE in CSMF (p> 0.05). The values of weight gain were: - 0.124, 0.316, 0.327 and 0.286 and CSMF were: 10.44, 9.99, 10.17 and 9.97 kg / day for T1, T2, T3 and T4 respectively. The SPE provided higher average weight gains compared to control (T1). A significant effect CSMT of T3 compared to T1, with 11.07 and 10.49 kg / day respectively. There was no effect of the substitution of urea by the conventional slow-release urea (ULL). The SPE provided better economic results than the control. The replacement of urea by the conventional slow-release urea (ULL) did not achieve better economic results.